Nurses' Attitudes Toward Caregiving Roles and Views on the Use of 'Robot Nurses': A Cross Sectional Study During the COVID-19 Pandemic - Neşe Altınok Ersoy; Adem Ersoy; Kürşat Murat Özcan (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study aimed to determine the nurses' attitudes toward caregiving roles and views on the use of robot nurses during the COVID-19 pandemic. Method: This descriptive and cross-sectional study was conducted with nurses providing care COVID-19 patients. The data were collected through an online survey using a sociodemographic form, a COVID-19 care form, and the Attitude Scale for Nurses in Caregiving Roles. Results: The total score on the Attitude Scale for Nurses in Caregiving Roles was 66 (SD=9.10); the scores on the self-care, safety, and treatment subscales were 4.06 (SD=0.65), 4.12 (SD=0.63), and 4.35 (SD=0.63), respectively. More than half of the nurses preferred the use of robot nurses to reduce the workload and the risk of severe infections. Conclusion: Even during the COVID-19 pandemic, nurses adopted caregiving roles and nursing robots could be used as a support to improve the quality of care.